αv Integrins combine with LC3 and atg5 to regulate Toll-like receptor signalling in B cells - Mridu Acharya; Anna Sokolovska; Jenny M. Tam; Kara L. Conway; Caroline Stefani; Fiona Raso; Subhankar Mukhopadhyay; Marianela Feliu; Elahna Paul; John Savill; Richard O. Hynes; Ramnik J. Xavier; et al. (Nature Communications, 2016)
Integrins can regulate antigen-specific and innate immune receptor signalling, thereby affecting immune cell function. Here the authors show that avß3 integrin controls Toll-like receptor (TLR) signalling by regulating its trafficking to limit TLR-mediated B-cell proliferation and antibody production.